Role of preoperative investigations in elderly patients undergoing oncosurgical procedures - A retrospective review audit - Bhagyalakshmi Ramesh; Viji S Pillai; Rachel C Koshy; K M Jagathnath Krishna (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: The aim of the study was to evaluate the efficacy and usefulness of the current practice of various investigations and consultations being done during preanesthetic evaluation in patients undergoing oncosurgical procedures in our hospital. We also evaluated the delay caused due to these and its value in predicting postoperative complications. Material and Methods: The preanesthetic charts of 300 elderly patients >65 years of age were reviewed, and the incidence of abnormal investigations and number of consultations advised were noted. The incidence and predictive values of these were assessed. Results: More than half the number of patients had more than one comorbidity and were advised various consultations based on history, National Institute of Clinical and Health Excellence (NICE) guidelines, and institutional protocol. Multiple visits to preanesthetic clinic were required in patients who had abnormal thyroid tests or respiratory complaints which was the main reason for delay in scheduling surgery. However, despite multiple comorbidities not more than 12.7% of the blood tests ordered were found to be abnormal. Abnormal blood tests were not significantly associated with higher incidence of postoperative complications. Conclusion: Blood investigations do not predict postoperative complication rate and do not influence anesthetic management of elderly patients undergoing oncosurgical procedures but are rather influenced by surgical procedure and presence of comorbidities. Hence, preanesthetic clinic should assess patients based on other predictive tests rather than relying on blood investigations alone.